Caracterização, estudo do processamento e conservação do mel de cacau. - Christiano Pedro Guirlanda (2022)
The demand for new antioxidants from natural products, fruits and their residues make cocoa honey an alternative for the economic use of by-products of cocoa production. Transparent in color, sour and sweet flavor, mucilaginous texture, it is rich in reducing sugars, dietary fibers, vitamin C and bioactive phenolic compounds with considerable antioxidant capacity, being a residue with potential for technological applications in the food industry. Cocoa and derivatives have always been used as a basis for the development of functional food and beverage formulations, but the content of bioactive compounds including polyphenols may vary depending on changes during post-harvest, technological processes and storage. New non-thermal processing technologies such as gamma irradiation, microwaves and freeze-dried differ from conventional technologies such as thermal pasteurization because they perform better in retaining the original characteristics of food and improve the efficiency of elimination of pathogens and allergens. Changes in the composition of processed products may occur during storage, with significant nutritional losses in addition to decreased quality. It was characterized the physicalchemical data such as ° Brix, pH, acidity, water activity and humidity in addition to the functional compounds for better definition of processing parameters. Comparing the processing technologies, thermal pasteurization was the process that most influenced the maintenance of the stability of bioactive compounds. The gamma irradiation dose of 3 kGy in addition to increasing the content of phenolic compounds in relation to the control of 424.3 mg of galic acid/100 g of cocoa honey to 431.3 galic acid/100 g of cocoa honey, ensured better maintenance of these compounds after storage at controlled temperature for 60 days. Aiming to value the use of cocoa honey in the industry, an exploratory study of spray drying technology was carried out to obtain cocoa honey powder. Drying conditions were evaluated using the same temperature and flow parameters but varying the proportion of carriers in the formulations with cocoa honey. Formulations with maldodextrin added whey protein (WPI) in the proportions 2:1 and 29:1, respectively, showed better results regarding final yield in addition to hygroscopicity. The formulation 29:1 maldodextrin plus WPI showed better retention of antioxidant compounds, compared to the former. Application of non-thermal technologies and obtaining cocoa honey powder with added protein in addition to adding nutritional and economic value to the by-product are potential innovations for cocoa culture and the food industry. These technologies can make up the processes for a biorefinery playing an important role in the sustainable development and enhancement of cocoa honey.